How do root fungi of Alnus nepalensis and Schima wallichii recover during succession of abandoned land? - Balami, Sujan; Vašutová, Martina; Chaudhary, Vijay Kumar; Cudlín, Pavel (Mycorrhiza, 2023)
Alnus nepalensis and Schima wallichii are native tree species accompanying succession in abandoned agricultural land in the middle mountainous region of central Nepal. To understand how root fungi recover during spontaneous succession, we analyzed the diversity and composition of arbuscular mycorrhizal (AM), ectomycorrhizal (ECM), and total fungi in tree fine roots from three land use types, short-term abandoned land (SA), long-term abandoned land (LA), and regenerated forest (RF) as a reference. Additionally, ECM morphotypes were examined. The results showed different speeds of succession in the studied fungal groups. While the change in the AM fungal community appears to be rapid and LA resembles the composition of RF, the total fungi in the abandoned land types are similar to each other but differed significantly from RF. Interestingly, the relative abundance of Archaeosporaceae followed a trend differing between the tree species (SA < LA in A. nepalensis, but SA > LA in S. wallichii). Unlike AM and total fungi, there was no significant difference in the ECM community of A. nepalensis between land use types, probably due to their low species diversity (9 ECM morphotypes, 31 ECM operational taxonomic units). However, Cortinarius sp. was significantly more abundant in RF than in the other land use types, whereas Alnicola, Tomentella, and Russula preferred young stages. Our results suggest that for both studied tree species the AM fungal succession could reach the stage of regenerated forest relatively fast. In the case of total fungi, because of hyperdiversity and composed of species specialized to a variety of environments and substrates, the transition was expected to be delayed in abandoned land where the vegetation was still developing and the ecosystem was not as complex as that found in mature forests.
Keywords: houby; Agaricales; Soil Microbiology; olše; ekosystém; Short-term and long-term abandoned soil; stromy; ECM morphotype; Trees; Fungi; půda; Ectomycorrhiza; Mycorrhizae; mykorhiza; půdní mikrobiologie; lesy; Nepal; Alnus; Arbuscular mycorrhiza; Ecosystem; Soil; Forests